Comoarative Study of Personality Traits for Elite National Female Footballers and Gymnasts - Jabar, Amar; Abedulameer, Athraa (Journal of Physical Education, 2007)
Building traits is the basics of building personality.for personality traits give consistency in behaviour and it make it predictable. Every sport needs individuals that have personality traits that suit that special sport.In gymnasts has to overcome have fears on her own when learning new movements.Such sport needs certain traits thate are different frome female footballers.Football is one of the theam sports that reguire a rather large number of players.Players of this game are chosen accourding to their basic skills and physical abilities.and above all they should be able to cooperate within amember of a team.The importance of the studt in identifying the personality traits differences between Elite female footballers and gymnasts. The aim of the study: 1. Identifying the personality traits of Elite national female gymnasts and footballers. 2. Making a comparison between the personality traity of the gymnasts and that of fenale footballers. The hypothesis was that there are statistical differences in some personality traits between female gymnasts and footballers.The subject of the study were (12) female players,(6) of them were gymnasts and the other (6) were footballers. The were tested using kattles’ test for personality traits that has (187) question testing (16) trait. The results showed significant differences between national elite female gymnasts and footballers in all traits corganization, sensitivity, control, anxiety, creativity and self-observation